Combination of Xuesaitong and Aspirin Based on the Antiplatelet Effect and Gastrointestinal Injury: Study Protocol for a Randomized Controlled Noninferiority Trial. (14th July 2021) - Zhu, Bao-Chen; Xue, Chun-Miao; Lang, Rui; Weng, Wei-Liang; Wang, Xu-Jie; Lei, Zhen-Zhen; Zhang, Sha-Sha; Yang, Wen-Hua; Zhang, Wan-Tong; Hua, Guo-Dong
Abstract : Background . Aspirin is the first-line medication for prevention and treatment of coronary heart disease (CHD). However, long-term use of aspirin resulting in gastrointestinal mucosal injury and bleeding limits the regularity of medication. Xuesaitong is a marketed Chinese medicine contained main active component in Panax notoginseng saponins (PNS), which can significantly inhibit platelet aggregation in patients with CHD. Our previous studies have already showed that PNS could reduce the gastrointestinal mucosal injury caused by aspirin in preclinical study. However, there is a need for further clinical studies to evaluate synergy and attenuation effect of the combination. Methods . This trial is a prospectively planned, open-labeled, parallel-grouped, single-centered clinical trial. A total of eligible 480 participants will be randomly allocated into three groups: aspirin group, Xuesaitong group, and drug combination group at a ratio of 1 : 1 : 1. The primary outcome is the change of platelet aggregation rate and calprotectin activity. Secondary outcomes include PAC-1, P-selectin, P2Y12, I-FABP activity, and fecal occult blood. Discussion . The results of the study are expected to provide evidence of high methodological and reporting quality on the synergy function of Xuesaitong and aspirin upon the antiplatelet and anti-gastrointestinal injury effect for CHD. It also provides an experimental basis for clinical rational drug combination therapy. Trial Registration . This trial was registered in the Chinese Clinical Trail Registry, ChiCTR2000036311, on 22 August 2020, http://www.chictr.org.cn/edit.aspx?pid=58798&htm=4 .